2009
DOI: 10.1002/art.24352
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1β and tumor necrosis factor α inhibit chondrogenesis by human mesenchymal stem cells through NF‐κB–dependent pathways

Abstract: Objective-The differentiation of mesenchymal stem cells (MSCs) into chondrocytes provides an attractive basis for the repair and regeneration of articular cartilage. Under clinical conditions, chondrogenesis will often need to occur in the presence of inflammatory mediators produced in response to injury or disease. Here we examine the effect of two important inflammatory cytokines, interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α), on the chondrogenic behavior of human MSCs.Methods-Aggregate cultures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
239
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(252 citation statements)
references
References 47 publications
11
239
0
2
Order By: Relevance
“…Many studies showed that cartilage degradation and pro-inflammatory pathways of OA are induced by the up-regulation of inflammatory cytokines [43][44][45]. Inflammatory cytokines, such as interleukin-1 (IL-1) and tumor necrosis factor (TNFa) [46], have been demonstrated to be upregulated after meniscus injury. Furthermore, an animal model of meniscus injury in rabbits showed that the elevated expression of IL-1 will last for at least 14 days [47], and upregulated inflammatory cytokines will in turn increase matrix metalloproteinase activity [48,49], proteoglycan release [50], as well as suppress collagen synthesis [51].…”
Section: Figmentioning
confidence: 99%
“…Many studies showed that cartilage degradation and pro-inflammatory pathways of OA are induced by the up-regulation of inflammatory cytokines [43][44][45]. Inflammatory cytokines, such as interleukin-1 (IL-1) and tumor necrosis factor (TNFa) [46], have been demonstrated to be upregulated after meniscus injury. Furthermore, an animal model of meniscus injury in rabbits showed that the elevated expression of IL-1 will last for at least 14 days [47], and upregulated inflammatory cytokines will in turn increase matrix metalloproteinase activity [48,49], proteoglycan release [50], as well as suppress collagen synthesis [51].…”
Section: Figmentioning
confidence: 99%
“…NFkB also seems to have relevant activities in initiating cells. To this end, it has been shown that inhibition of this transcription factor maintains pluripotency of mouse embryonic-initiating cells (Torres and Watt, 2008), promotes condrogenesis by human mesenchymal-initiating cells (Wehling et al, 2009) and controls the number of neural progenitor cells (Widera et al, 2006;Young et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence indicating that proinflammatory cytokines, and particularly IL-1, play an important role in the pathogenesis of OA (17)(18)(19), as well as the inhibition of mesenchymal stem cell (MSC)-based repair of cartilage (20)(21)(22)(23)(24)(25). However, natural inflammatory modulators such as IL-1 receptor antagonist (IL-1Ra) can inhibit IL-1 signaling (26), and studies have shown that biomaterial-mediated delivery of IL-1Ra can mitigate the degradative effects of IL-1 (27).…”
mentioning
confidence: 99%